Solitary Cardiac Low-Grade Neuroendocrine Tumor: A Case Report and Review of the Literature. (28th October 2020) - Kavesh, M; Drew, P; Stewart, B
Abstract: Introduction/Objective: Primary tumors of the heart are uncommon; even rarer are primary cardiac neuroendocrine tumors. To our knowledge, only two cases have been described to date, both being high-grade tumors. We report a solitary low-grade neuroendocrine tumor of the heart, unexpectedly discovered on the wall of the right ventricle in a 44-year-old man during aortic valve repair for infectious bacterial endocarditis. Results: Frozen section was sent intraoperatively and showed a plasmacytoid neoplasm. Final pathology of the biopsies showed a tumor composed of both cohesive and discohesive plasmacytoid cells separated by a vascular network and strands of fibrosis. Neither necrosis nor a mitotic rate greater than 2 mitoses per 2 mm 2 were seen. The tumor showed strong reactivity for AE1/3, synaptophysin and CDX2 with focal reactivity for chromogranin-A and CD56, confirming the diagnosis of a low-grade neuroendocrine tumor. Both an esophagogastroduodenoscopy and colonoscopy were performed and showed no evidence of a primary gastrointestinal tumor. PET-CT DOTATATE performed after complete resection of the tumor showed no abnormal radiotracer uptake. The possibility of an intestinal neuroendocrine tumor undetected by DOTATATE PET-CT with a single known metastasis to the heart was considered. This too, on the basis of the literature, was considered exceedingly rare. Complete resection of this patient's tumor was considered sufficient treatment; the patient was advised to follow up annually with medical oncology. Conclusion: The presentation and management of a solitary cardiac low-grade neuroendocrine tumor has not previously been described in the literature.